The relationship between office environment and employee’s productivity among administrative staff at University Teknologi Mara Campus Jengka, Pahang / Nurul Syafikah Hanim Mustaffa - Mustaffa, Nurul Syafikah Hanim (Faculty of Business and Management, 2017)
All degrees students form faculty business management in office system must do research about certain topic to complete our degree. Therefore the purpose of this research identify the relationship between office environment and employee’s productivity in University Teknologi MARA Campus Jengka, Pahang. The questionnaires were prepared and researcher distributed and used as instrument to collect will be analysed in IBM SPSS Statistics 23.0 soft. There are 75 from administrative staff in Universiti Teknologi MARA Campus Jengka, Pahang that are been choosing as a respondent. This research paper was used a convenience sampling. There are some recommendations that can be implementing by Universiti Teknologi MARA Campus Jengka, Pahang to improve the employee’s productivity, Thus, the researcher for future research should conduct study at other branch of Universiti Teknologi MARA industry to find the variety of the finding their research